Patient characteristics and the lifetime risk of revision following knee and hip replacement: evidence from routinely-collected data - Burn, E; Arden, N; Edwards, C; Cooper, C; Murray, D; Prieto-Alhambra, D; Pinedo Villanueva, R (EFORT, 2018)
Revision surgery following joint replacement is associated with both morbidity for patients and high costs for the health care system. The impact of patient characteristics on the lifetime risk of revision, however, is not well-known.